Visual Contextual Effects of Orientation, Contrast, Flicker, and Luminance: All Are Affected by Normal Aging - Nguyen, Bao N.; McKendrick, Allison M. (Frontiers in Aging Neuroscience, 2016)
The perception of a visual stimulus can be markedly altered by spatial interactions between the stimulus and its surround. For example, a grating stimulus appears lower in contrast when surrounded by a similar pattern of higher contrast: a phenomenon known as surround suppression of perceived contrast. Such center-surround interactions in visual perception are numerous and arise from both cortical and pre-cortical neural circuitry For example, perceptual surround suppression of luminance and flicker are predominantly mediated pre-cortically, whereas contrast and orientation suppression have strong cortical contributions. Here we compare the perception of older and younger observers on a battery of tasks designed to assess such visual contextual effects. For all visual dimensions tested (luminance, flicker, contrast, orientation), on average the older adults showed greater suppression of central targets than the younger adult group. The increase in suppression was consistent in magnitude across all tasks, suggesting that normal aging produces a generalized, non-specific alteration to contextual processing in vision.